Enhanced heroin analgesic effect in male offspring of sires who self-administered heroin - Gao, Wenjing; Pan, Tao; Fan, Guangyuan; Cui, Jian; Wang, Tingting; Huang, Nan; Jiang, Changyou; Ma, Lan; Wang, Feifei; Liu, Xing; Le, Qiumin (Frontiers in Pharmacology, 2023)
A growing body of evidence indicates that parental drug abuse, even occurring before conception, could induce phenotypic changes in the offspring. It has been shown that parental opioid exposure affects developmental processes, induces memory deficits, and results in psycho-emotional disorders in descendants. However, how parental, especially paternal, chronic drug exposure affects offspring remains unexplored. In the current study, we explored the effects of paternal 31-day heroin self-administration experience on the offspring. The body weight and litter size of the Heroin F1 generation were not changed, compared with the Saline F1 generation. Furthermore, paternal chronic heroin self-administration experience had no significant impact on object-based attention tests or cocaine self-administration behavior in either sex However, in the hot plate test, although no difference in basal latency between the two groups was detected in either sex, a significant increase in the analgesic effect of heroin in the male Heroin F1 generation was observed. Collectively, these data provide evidence that paternal chronic heroin self-administration experience could sex-dimorphically increase the analgesic effect of heroin in male offspring, but had no significant impact on response to cocaine reinforcement or attention behavior.